Metallomics and NMR-based metabolomics of Chlorella sp. reveal the synergistic role of copper and cadmium in multi-metal toxicity and oxidative stress1. Issue 3 (11th March 2015) - Zhang, Wenlin; Tan, Nicole G. J.; Fu, Baohui; Li, Sam F. Y.
<x xml:space="preserve">Abstract</x> Metallomics and NMR-based metabolomics reveal the synergistic role of Cu and Cd in multi-metal microalgae toxicity by inducing oxidative stress, which leads to photosynthesis inhibition and cell toxicity.